Accessing substituted pyrrolidines via formal [3+2] cycloaddition of 1, 3, 5-triazinanes and donor-acceptor cyclopropanes. Issue 8 (21st February 2018) - Chu, Zhi-Yao; Li, Na; Liang, Dan; Li, Zheng-Hui; Zheng, Yong-Sheng; Liu, Ji-Kai
Graphical abstract: Highlights: Formal [3+2] cycloaddition of 1, 3, 5-triazinanes and donor-acceptor cyclopropanes. Highly efficient, mild approach for the synthesis of substituted pyrrolidines. Broad substrates scope of 1, 3, 5-triazinanes and donor-acceptor cyclopropanes. Illumination of the reaction mechanism. Successful demonstration of gram scale synthesis. Abstract: The formal [3+2] cycloaddition of 1, 3, 5-triaryl-1, 3, 5-triazinanes with donor-acceptor cyclopropanes has been found to provide pyrrolidines in good to excellent yields under mild reaction conditions. Preliminary mechanistic investigation indicates that this formal [3+2] cycloaddition reaction proceeds through competing SN 1 and SN 2 pathways.